Evaluasi Penerapan Kurikulum 2013 di SMK Negeri 1 Payakumbuh - Rina Novalinda; Nizwardi Jalinus; Jalius Jama (Universitas Pancasakti Tegal, 2020)
This research goal is to describe the implementation of the 2013 curriculum, especially in natural science subjects at SMK Negeri 1 Payakumbuh. The 2013 curriculum is one of the government's strategies to improve the quality of education. Payakumbuh State Vocational School 1 is one of the schools that have implemented or implemented the curriculum since 2014. This evaluation research departs from a roblem found in the implementation of the 2013 curriculum in Vocational School 1 Payakumbuh, especially science. The subjects of this study were students and science teachers at SMK Negeri 1 Payakumbuh. Data collection techniques used in this study were observation, interviews, questionnaires, and documentation. The data analysis technique used in this research is descriptive qualitative. This research describes how the implementation of the 2013 curriculum in schools is based on the staskeholder countenance evaluation model and is guided by the standards used. The results showed that: 1). In the preliminary stage, 100% meet the standards of the 2013 Curriculum tool and learning planning; 2). At the transaction stage, 40% did not meet the conditions for learning implementation and 40% did not meet the standards for authentic assessment; 3). At the yield stage, 83.3% did not meet the provisions for authentic assessment results